Factors Affecting Employee Performance in Providing Online Tax Reporting Services - Ahmad Ilham Robbani; Ahmad Nurul Fajar (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In recent years, there have been many cases related to the Directorate General of Taxes. This phenomenon is to find out whether the use of a good management information system can affect employee performance in order to minimize cases such as those carried out by tax employees today. This study aims to analyze the influence of management information systems and knowledge management elements on the performance of KPP (Tax Service Office) employees in a company. The method used is quantitative with a survey approach, involving all active employees as samples through saturated sampling techniques. Testing was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of the study showed that explicit knowledge management and structured training were important factors in improving employee performance. Meanwhile, organizational culture and implicit knowledge showed a positive influence, but were not strong enough to significantly drive performance. Meanwhile, emotional intelligence and competence have not shown optimal contributions to improving performance. These findings underline the importance of focusing on strengthening the knowledge documentation system and ongoing training as the main strategy for improving the performance of tax officials, especially in the era of digitalization of public services.